Understanding reactions and pore-forming mechanisms between waste cotton woven and FeCl3 during the synthesis of magnetic activated carbon. (February 2020) - Xu, Zhihua; Zhou, Yuwei; Sun, Zhenhua; Zhang, Daofang; Huang, Yuanxing; Gu, Siyi; Chen, Weifang
Abstract: FeCl3 is a valuable iron salt used in the synthesis of magnetic waste cotton woven-based activated carbon. Although it has received extensive research attention, more information is required regarding its interactions with the carbon matrix. This systematic study describes the potential reactions of FeCl3 and waste cotton woven. First, the textural properties of waste cotton woven-based activated carbon synthesized under various conditions were investigated via element analysis, N2 sorption/desorption isotherms, and scanning electron microscopy. Then, the possible reaction mechanisms were deduced through various characterization methods. The results demonstrate that FeCl3 can lower the initial decomposition temperature of WCW to 135 °C and catalyze decarboxylation and decarbonylation at 100–330 °C to elevate the formation of microporous structures. Moreover, FeCl3 can also form Lewis acid sites at 330–700 °C and promote the cross-linking reaction to develop intricate microporous structures and carbonaceous materials with the synergistic effect of Fe 3+ and Cl − . FeCl3 could be used as a template-like agent to form mesoporous structures. Meanwhile, it can also act as a magnetizer that Fe3 O4 derived from the decomposition of FeCl3 would insert into the carbon matrix and combine with C–Cl to tailor the magnetic controllable activated carbon. Finally, we confirmed that extending the activation time could convert the structure of waste cotton woven-based activated carbon and increase the number of active sites, thereby further improving the catalytic properties of FeCl3 in pore formation. Graphical abstract: Image 1 Highlights: FeCl3 reduced the initial pyrolysis temperature of waste cotton woven. The catalysis of FeCl3 promoted the cleavage of long-chain hydrocarbons. The synergistic effect of Fe 3+ and Cl − accelerated the cross-linking reaction. FeCl3 acted as a template-like agent contributed to mesoporous development.